Streptococcus pyogenes disease and molecular pathogenesis - Cleary, P. Patrick (Henry Stewart Talks, 2009)
Important Streptococcal species, S. pyogenes: the chain that links the throat to the heart, Life threatening complications, Rheumatic fever, Acute post streptococcal glomerulonephritis, Invasive S. pyogenes disease, Strep throat activates psoriasis and obsessive compulsive behavior, Identification of group A streptococcus, S. pyogenes expresses a complex array of factors that interact with host defenses, Molecular mimicry hides bacterium from host's defenses, Key complement components, Destruction of host chemotactic signals is critical for initiation of infection, C5a peptidase, M protein, Tonsils are reservoir for recurrent infection, Superantigens